2013
DOI: 10.1371/journal.pone.0079723
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Orientation Continuity and Discontinuity by Cat V1 Neurons

Abstract: The orientation tuning properties of the non-classical receptive field (nCRF or “surround”) relative to that of the classical receptive field (CRF or “center”) were tested for 119 neurons in the cat primary visual cortex (V1). The stimuli were concentric sinusoidal gratings generated on a computer screen with the center grating presented at an optimal orientation to stimulate the CRF and the surround grating with variable orientations stimulating the nCRF. Based on the presence or absence of surround suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Adult cats of both sexes were used for these experiments. Surgical procedures and animal preparation have been described previously [7].…”
Section: Animal Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Adult cats of both sexes were used for these experiments. Surgical procedures and animal preparation have been described previously [7].…”
Section: Animal Preparationmentioning
confidence: 99%
“…Previous studies have suggested that the center responses of the majority of V1 cells are suppressed by the inclusion of surround stimuli. We named these neurons "surround-suppressive" (SS) cells [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed descriptions of animal surgery, anesthesia, and recording techniques can be found in previous studies [25,26] . Briefl y, cats were anaesthetized prior to surgery with ketamine hydrochloride (30 mg/kg, i.v.…”
Section: Animal Preparationmentioning
confidence: 99%